2021
DOI: 10.1002/ange.202107855
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Isomers: Enhanced Antiaromaticity/Diradical Character versus Deleterious Ring‐Opening of Benzofuran‐fused s‐Indacenes and Dicyclopenta[b,g]naphthalenes

Abstract: We examine the effects of fusing two benzofurans to s‐indacene (indacenodibenzofurans, IDBFs) and dicyclopenta[b,g]naphthalene (indenoindenodibenzofurans, IIDBFs) to control the strong antiaromaticity and diradical character of these core units. Synthesis via 3‐functionalized benzofuran yields syn‐IDBF and syn‐IIDBF. syn‐IDBF possesses a high degree of paratropicity, exceeding that of the parent hydrocarbon, which in turn results in strong diradical character for syn‐IIDBF. In the case of the anti‐isomers, syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 47 publications
(99 reference statements)
0
9
0
Order By: Relevance
“…However, the majority of the PCHs (with or without substituted heteroatoms) have a small-to-moderate open-shell character and possess a singlet ( S = 0) ground state due to the double-spin polarization 26 with a low-lying triplet excited state. 5,25,27–42 Recent studies on high-spin substituted PCHs report a triplet ( S = 1) ground state (Fig. 1d and e), showing the possibilities to design hydrocarbon-based materials with magnetic properties.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…However, the majority of the PCHs (with or without substituted heteroatoms) have a small-to-moderate open-shell character and possess a singlet ( S = 0) ground state due to the double-spin polarization 26 with a low-lying triplet excited state. 5,25,27–42 Recent studies on high-spin substituted PCHs report a triplet ( S = 1) ground state (Fig. 1d and e), showing the possibilities to design hydrocarbon-based materials with magnetic properties.…”
Section: Introductionmentioning
confidence: 96%
“…32,45 Optimization of s -indacene's molecular structure and properties involving the substitution of bulky tert -butyl groups to kinetically block the reactive sites 46 and fusion of external five-/six-membered rings to extend the π-conjugation path served as the most proficient strategies. 30–32,34,40,47–49 The fusion of external rings modulates the paratropicity of the s -indacene core, reducing the highest occupied molecular orbital (HOMO)–lowest unoccupied molecular orbital (LUMO) energy gap. 31,32,40 Our recent study, 50 where we have thoroughly investigated the relationship between the HOMO–LUMO energy gap and open-shell character, showed that molecules with a smaller HOMO–LUMO energy gap provide a more open-shell character.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations